2012
DOI: 10.1016/j.dr.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of children’s testimony in the era of developmental reversals

Abstract: A hoary assumption of the law is that children are more prone to false-memory reports than adults, and hence, their testimony is less reliable than adults’. Since the 1980s, that assumption has been buttressed by numerous studies that detected declines in false memory between early childhood and young adulthood under controlled conditions. Fuzzy-trace theory predicted reversals of this standard developmental pattern in circumstances that are directly relevant to testimony because they involve using the gist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 150 publications
(141 reference statements)
3
59
0
5
Order By: Relevance
“…Our findings have some interesting forensic implications. Historically, scientific evidence has indicated that children's testimony is more likely to be affected by false memories than adults' (Brainerd & Reyna, 2012;Ceci & Bruck, 1993). What the extant research on developmental trends in spontaneous false memories suggests is that this assumption is untenable when it comes to spontaneous false memories .…”
Section: Hit Rates and False Recognitionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings have some interesting forensic implications. Historically, scientific evidence has indicated that children's testimony is more likely to be affected by false memories than adults' (Brainerd & Reyna, 2012;Ceci & Bruck, 1993). What the extant research on developmental trends in spontaneous false memories suggests is that this assumption is untenable when it comes to spontaneous false memories .…”
Section: Hit Rates and False Recognitionmentioning
confidence: 92%
“…Why the DRM paradigm also attracts much scientific attention is because studies show that the DRM illusion is related to false autobiographical memories which implies that this task could be used to make inferences about autobiographical memory (Gallo, 2010; but see also Otgaar & Candel, 2011). Furthermore, developmental studies using the DRM paradigm show an age-related increase in the production of false memories with children being less susceptible to DRM false memories than adults Brainerd & Reyna, 2012;Howe et al, 2009). This developmental reversal in spontaneous false memories has been obtained in a growing number of studies on children's false memory development (e.g., Brainerd & Reyna, 2007;Howe, 2007;Otgaar & Smeets, 2010).…”
mentioning
confidence: 99%
“…When subsequently asked to remember the words on the list, both children, and to a greater extent adults, frequently remember many of the presented words along with the unpresented critical lure. Thus, like true memories, false memory production also increases with age (see Brainerd & Reyna, 2012;Howe, 2011b).…”
Section: True and False Memoriesmentioning
confidence: 99%
“…En la actualidad, las pruebas disponibles sugieren que los niños, a medida que van avanzando en edad, son más exactos a la hora de contestar preguntas, a la vez que más resistentes a las sugestiones que pudieran incluir esas preguntas (Brainerd & Reyna, 2012;Bruck & Ceci, 1999). Los resultados del estudio van en esta línea, ya que los preescolares de 3 años fueron vulnerables en un doble sentido (hipótesis 1a y 1b): su memoria para lo ocurrido fue más pobre y, a la vez, aceptaron más acciones falsas sugeridas que los mayores (4 y 5 años).…”
Section: Edadunclassified
“…En las últimas décadas, con independencia de la naturaleza del paradigma de sugestionabilidad empleado, la investigación ha proporcionado pruebas claras de que los preescolares son particularmente susceptibles a los efectos contaminantes de la información falsa proporcionada por los entrevistadores a través de las preguntas que dirigen a los niños 1 acerca de sus experiencias previas (Brainerd & Reyna, 2012;Bruck & Ceci, 1999;Ceci, Bruck, & Battin, 2000;Ceci, Ross, & Toglia, 1987;Poole & Lamb, 1998). De hecho, está bien establecido que la edad es uno de los factores más relevantes implicados en la memoria y la aceptación de la sugestión.…”
Section: Introductionunclassified